OP82 #Population priorities for successful ageing: a randomised vignette experiment. (September 2018) - Whitley, E; Benzeval, M; Popham, F
Abstract : Background: Worldwide population ageing has resulted in a growing interest in 'successful ageing' but there is no established consensus as to what this entails. Existing evidence is largely qualitative, confounded, and restricted to older ages. We aimed to provide robust, unconfounded estimates of the relative importance placed by the general population on six commonly-used dimensions of successful ageing (disease, disability, physical functioning, cognitive functioning, interpersonal engagement, and productive engagement). Methods: We conducted a randomised experiment in wave 9 of the Understanding Society Innovation Panel, a stratified, geographically clustered sample of 2545 men and women designed to be representative of the British population. A total of 2010 (79%) respondents took part in the experiment and were presented with three vignettes, each describing a hypothetical 75 year old person with randomly determined favourable or unfavourable outcomes for each of the six dimensions. Respondents were asked how successfully the person described was ageing on a scale from 0 (not successfully) to 10 (very successfully). Results: The main outcome measure for each of the dimensions was the difference in mean scores comparing vignettes with favourable versus unfavourable attributes; as each dimension was presented in the same way, direct comparisons can be made between them to understand their relative importance. Scores were allocated to 5967 vignettes and those in which dimensions were favourable were allocated higher scores than those in which they were unfavourable. However, the relative importance given to each dimension varied. Across all participants, the largest differences were observed for cognitive function (difference (95% CI): 1.20 (1.11, 1.30)) and disability (1.18 (1.08, 1.27)) and the smallest for disease (0.73 (0.64, 0.82)) and productive engagement (0.58 (0.49, 0.66). Differences for physical functioning and interpersonal engagement were 0.82 (0.73, 0.90) and 0.99 (0.89, 1.08) respectively. Responses were consistent across vignette gender and most respondent characteristics. However, the relative importance given to different dimensions varied with respondent's age. Differences for social engagement remained fairly constant at all ages, while the relative importance of disease decreased somewhat with increasing age. In contrast, differences for physical function, cognitive function, and productive engagement increased with increasing age. Conclusion: Clinical definitions of successful ageing that focus on longevity and disease do not reflect the views of the general population. In order to support and promote successful ageing, practitioners and policy makers should be aware of older people's priorities for ageing and, in particular, understand how these differ from their own.